Pengembangan Model Bisnis UMKM dan Strategi Pemasarannya - Andhatu Achsa; Diar Marlina Verawati; Ivo Novitaningtyas (Universitas Airlangga, 2023)
This research aims to formulate marketing strategies and develop business models for SMEs in Tourism Village, that is Ngargogondo Village. This research was conducted based on a qualitative descriptive approach for exploratory purposes. Primary data was obtained based on interviews and observations, secondary data was obtained from literature and government documents. Data was analyzed based on SWOT analysis and Business Model Canvas (BMC). The research results show that SMEs in Ngargogondo Village need to improve product aspects, marketing communication aspects and distribution aspects. The products offered require increased innovation and diversification to support the value proposition. In marketing, social media influencers are needed to increase audience awareness of these SME products and to improve distribution channels. The research results provide managerial implications for SME owners to implement innovative marketing strategies. By implementing the proposed strategy related to marketing aspects, SMEs in Ngargogondo Village are expected to develop and be sustainable to support Borobudur as a national tourism strategic area. The research results also provide theoretical implications in the form of methods that can be used to formulate marketing strategies and develop SME business models. Future research can replicate the method or combine it with other strategy formulation tools.